1995
DOI: 10.1007/bf00932417
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes carrying mutations in spectrin and protein 4.1 show differing sensitivities to invasion byPlasmodium falciparum

Abstract: The role of the erythrocyte skeleton in the invasion process of Plasmodium falciparum was evaluated using genetically variant erythrocytes containing well-defined molecular defects in alpha spectrin (alpha Sp) or protein 4.1 from eight unrelated families. Invasion into red cells from subjects of three black families with hereditary pyropoikilocytosis (HPP) due to inheritance of alpha I/74 mutant spectrin was significantly reduced in cells both from the patients and from the relatives of these who carried asymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Indeed, erythrocytes with naturally unstable membranes (e.g., hereditary spherocytosis, hereditary pyropoikilocytosis, hereditary elliptocytosis, Asian ovalocytosis) do not support Plasmodium proliferation in vitro [32,37–40]. Furthermore, treatment of red cells with morphology-altering drugs has been shown to inhibit entry and maturation of the parasite in cell culture [41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, erythrocytes with naturally unstable membranes (e.g., hereditary spherocytosis, hereditary pyropoikilocytosis, hereditary elliptocytosis, Asian ovalocytosis) do not support Plasmodium proliferation in vitro [32,37–40]. Furthermore, treatment of red cells with morphology-altering drugs has been shown to inhibit entry and maturation of the parasite in cell culture [41].…”
Section: Discussionmentioning
confidence: 99%
“…We collected blood samples from 121 donors with no known history of blood disorders, most of whom self-identified as having recent African ancestry (Figure 1A). As a positive control, we also sampled a patient with hereditary elliptocytosis (HE), a polygenic condition characterized by extremely fragile RBC membranes that strongly inhibit P. falciparum growth (Schulman et al, 1990;Facer, 1995;Dhermy et al, 2007;Gallagher, 2013). We performed whole-exome sequencing (Figure 1-source data 1), both to check for the presence of known RBC disease alleles and to confirm the population genetic ancestry of our donors.…”
Section: Many Healthy Blood Donors With African Ancestry Carry Alleles For Rbc Diseasementioning
confidence: 99%
“…Plasmodium relies on a favourable host environment in order to thrive, many erythrocyte-related polymorphisms have been discovered that interfere with parasite survival thus contributing to malaria resistance. These include polymorphisms that affect the cytoskeleton of erythrocytes, such as Southeast Asian Ovalocytosis (SAO), hereditary elliptocytosis (HE) and spherocytosis (HS)910111213. Several hypotheses have been proposed for the mechanisms by which they confer malaria protection, including reduced erythrocyte invasion, intra-erythrocytic growth and cytoadherence813141516171819.…”
mentioning
confidence: 99%
“…However, due to the heterogeneity of the manifestation of these disorders in the human population, contradicting evidences for resistance mechanisms has often been presented. A study done by Facer13 showed that only patients carrying certain spectrin mutations have impaired parasite invasion of red blood cells (RBC), but not others that also exhibited HE symptoms. A similar observation was reported by Chishti, et al 17, where individuals with defective protein 4.1 exhibited intra-erythrocytic growth inhibition, but not those with glycophorin C defects, despite the fact that both defects gave rise to HE.…”
mentioning
confidence: 99%